Height Propagation Law and Controlling Strategies of Acid Fractures in Carbonate Gas Reservoirs With Bottom Water Layer Under Different Stress Profiles - Jian Yang; Weihua Chen; Zixi Jiao; Jiexiao Ye; Song Li; Qiuyun Hu; Haiyan Zhu; Zhaopeng Zhang (Geofluids)
Acid fracturing is currently employed to develop the carbonate gas reservoir in the second section of the Dengying Formation at the Anyue Gas Field, Sichuan Basin. However, improper acid-fracturing operational parameters pose a risk of fracture communication with the bottom water layer, leading to increased water production and a significant decline in gas productivity. In this study, numerical simulations were performed using FracPro PT software, taking into account the geological characteristics of the second section of the Dengying Formation. The analysis considered various in situ stress profiles and different vertical distances to the bottom water layer (Hw) to explore effective strategies for controlling fracture height during acid treatment. The results indicate that injection volume, injection rate, permeability, stress difference between the reservoir and the barrier (Δσ), and acid viscosity are the key factors affecting fracture height growth. When the reservoir stress is 4 MPa higher than that of the barrier and Hw is less than 70 m, it is recommended to construct an artificial barrier above the bottom water layer to increase Δσ by 4.0 to 5.0 MPa and to inject 160 m3 of gelled acid at a rate of 5.0 to 6.0 m3/min to prevent fracture communication with the bottom water layer. Conversely, when reservoir stress is 4 MPa lower than the barrier and the vertical distance Hw is greater than 50 m, over 200 m3 of gelled acid can be injected at a rate exceeding 6.0 m3/min to achieve the largest stimulated reservoir volume due to effective containment by the barriers. Furthermore, when the stress gradient is positive (e.g., 113–115–117 MPa) and Hw exceeds 30 m, more than 200 m3 of gelled acid can be injected at a rate greater than 7.0 m3/min, benefiting from the barrier effect of the lower layer. On the other hand, for a negative stress gradient (e.g., 117–115–113 MPa) and Hw less than 50 m, an artificial barrier must be established to increase Δσ by at least 6.0 MPa. In this scenario, a limited acid volume of 120 m3 is recommended, injected at a rate of 7.0 to 8.0 m3/min to avoid excessive fracture height growth reaching the bottom water layer. Based on the optimal acid treatment strategy for controlling fracture height, a field application was carried out at the Gaoshi-X well. The initial daily production rate reached 17.6×104 m3/day and subsequently stabilized at 13.5×104 m3/day, achieving both high and stable production. The conclusions drawn from this study aim to provide theoretical guidance for optimizing acid-fracturing designs in carbonate gas reservoirs with bottom water, ultimately enhancing production effectiveness while mitigating associated risks.